Common Peafowl (Pavo cristatus) Farming in Bangladesh: Current Status, Reproductive Behavior and Health Management (Journal of Science and Technology Research, 2024)
The research was carried out in a few selected regions of Bangladesh from July 2022 to June 2023 to explore the current status, reproductive behavior, and health management of captive common peafowl (Pavo cristatus). Ten peafowl farmers were interviewed using pre-structured questionnaire to collect primary data. The data were processed, and then illustrated in tabular form employing descriptive statistical analyses. The majority of the farmers were aged between 31 to 50 years, with 50% engaged in business. They became interested in peafowl farming through social media, other farmers, and friends. Notably, most of the farmers reared India Blue variety of common peafowl. They had neither prior experience nor participated in any training programs on peafowl farming. The adult male peafowl (peacock) significantly (P